Pengaruh Penggunaan Website UIN KHAS Terhadap Kemudahan Akses Informasi Mahasiswa MPI UIN KHAS Jember - Manzil Silsa Sabila; Intan Nurlaili Thoyyibah; Gesha Ayu Hanafiah; Qudwatun Hasanah; Rofiq Hidayat (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to identify and analyze the influence of using the Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember (UINKHAS) website on the ease of access to information for students. Using a quantitative approach with a causal comparative research type, data were collected through online questionnaires from 30 students of the Islamic Education Management (MPI) study program at the Faculty of Tarbiyah and Teacher Training. The analysis results showed that all items in the questionnaire were valid and reliable. Classical assumption tests indicated no issues of normality, heteroscedasticity, and multicollinearity. Hypothesis testing through multiple linear regression indicated that the use of the UINKHAS website has a significant and positive effect on the ease of access to information, with a determination coefficient of 92.3%. These findings reinforce the importance of utilizing information technology to enhance the efficiency and effectiveness of information access in higher education.